(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article reveals the essence of issues such as the problem of good and evil, the role of knowledge in human development, acquiring a profession, preserving the strength of the family, and striving for knowledge and enlightenment, which are considered the main spiritual and moral values in the teachings of Mahmudkhoja Behbudi.